From grammatical to pragmatic competence - Radovanović, Aleksandra (Vestnik za tuje jezike, 2018)
To start reducing the probable discrepancy between English for Tourism Purposes (ETP) learners' pragmatic and grammatical development, the pragmatic facets of the polyvalent grammatical categories should be reflected in the instruction. The study focused on tense and aspect with two complementary aims: 1) to identify and set forth a characterization of tense and aspectual verbal forms used as the internal pragmatic modifiers contributing to politeness in ETP, and 2) to highlight the relevant points and outline the proposals for ETP teachers. The listening scripts from four textbooks were used in an analysis primarily oriented towards pragmalinguistics. The study confirmed the association between the investigated linguistic items and politeness, and provided the theoretical account of the hypothetical past, past tense and progressive aspect, but also shed light on the politeness effects conveyed by future-reference verbal forms. It also suggested an approach in ETP instruction based on raising students' pragmatic awareness.
Keywords: angleščina; aspekt; didaktika jezika; glagolski čas; glagolski vid; jezik stroke; pragmatična zmožnost; strokovni jezik; turizem; vljudnost